Factor XI deficiency is not associated with an increased risk of pneumonia and pneumonia‐related mortality. Issue 4 (2nd April 2018) - Salomon, O.; Preis, M.; Abu Shtaya, A.; Kotler, A.; Stein, N.; Saliba, W.
Abstract : Introduction: Drugs targeting factor XI (FXI) shows promising results in reducing postoperative VTE. Recently, researchers have shown that FXI knockout mice had a worse outcome when infected with pathogens for pneumonia, raising concerns about the safety of these drugs. Aim: To investigate the effect of FXI deficiency on the incidence of pneumonia and outcomes of pneumonia in humans. Methods: Using the computerized database of the largest healthcare provider in Israel, we identified adults who were tested for FXI activity between January of 2002 and December of 2014 (n = 10 193). Patients were followed up until December of 2016 for the occurrence of pneumonia and pneumonia requiring hospitalization as a proxy of severe pneumonia. Results: A total of 8958 (87.9%) had normal FXI activity, 804 (7.9%) had partial deficiency and 431 (4.2%) had severe deficiency; 722 individuals had pneumonia during 70 881 person‐years of follow‐up (incidence rate: 10.2 per 1000 person‐years). Compared to those with normal FXI activity, the adjusted HR for pneumonia was 0.87 (95% CI, 0.67‐1.14), and 0.95 (0.69‐1.30) for those with partial and severe FXI deficiency, respectively. Overall, 256 individuals were hospitalized for pneumonia during 72 209 person‐years of follow‐up (incidence rate: 3.5 per 1000 person‐years). The corresponding HR for severe pneumonia was 1.0 (0.70‐1.48) and 0.86 (0.53‐1.40) in those with partial and severe FXI deficiency, respectively. FXI deficiency was not significantly associated with 30‐day and 90‐day mortality among patients with pneumonia. Conclusion: FXI deficiency was not associated with an increased risk of pneumonia, pneumonia severity or short‐term mortality among patients with pneumonia.